2021
DOI: 10.1039/d1na00439e
|View full text |Cite
|
Sign up to set email alerts
|

A platinum nanoparticle doped self-assembled peptide bolaamphiphile hydrogel as an efficient electrocatalyst for the hydrogen evolution reaction

Abstract: Noble metal-based nanomaterials have shown great potential for catalytic application with higher selectivity and activity. Owing to the self-assembly properties with various molecular interactions, peptides play an essential role in...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 78 publications
0
18
0
Order By: Relevance
“…S3c†) shows two characteristic peaks at 532.9 and 531.6 eV, which are attributed to O–C–O and C–O bonding interactions present in the peptide bolaamphiphile, respectively. 54 Moreover, two additional peaks appeared at 534.9 and 532.5 eV suggesting the presence of PdO and C–O–Pd bonding interaction which substantially overlap with O 1s bands. 71 The XPS measurement confirms successful conversion of Pd( ii ) to Pd(0) and the generation of Pd NPs within the matrix of peptide bolaamphiphiles.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…S3c†) shows two characteristic peaks at 532.9 and 531.6 eV, which are attributed to O–C–O and C–O bonding interactions present in the peptide bolaamphiphile, respectively. 54 Moreover, two additional peaks appeared at 534.9 and 532.5 eV suggesting the presence of PdO and C–O–Pd bonding interaction which substantially overlap with O 1s bands. 71 The XPS measurement confirms successful conversion of Pd( ii ) to Pd(0) and the generation of Pd NPs within the matrix of peptide bolaamphiphiles.…”
Section: Resultsmentioning
confidence: 98%
“…Hydrogel and Pd@hydrogel electrodes were obtained according to previously reported work. 54 A piece of conducting CP (1 × 1 cm 2 ) was immersed into a solution of 1 M HCl and ultrasonicated for 10 min, followed by washing with a copious amount of methanol to eliminate the organic matter. Subsequently, CP was dried in an oven at 70 °C for 2 h. Typically, 10 mg of the lyophilized xerogel of Pd@hydrogel was added to 0.5 mL (4 : 5 v/v) ethanol/water mixture and ultrasonicated for about 20 min.…”
Section: Methodsmentioning
confidence: 99%
“…Although less reported in the literature, other materials can be incorporated to benefit peptide hydrogels in terms of structural and functional properties. Metals such as palladium (Pd) and platinum (Pt) are among them, with applications revolving around catalysis [148][149][150][151][152][153]. For example, Maity's group developed a hydrogel from a tyrosine and tryptophan-based bolaamphiphile that was used as a template for the synthesis of Pd nanoparticles [148].…”
Section: Composites For Electronic Catalytic and Environmental Applic...mentioning
confidence: 99%
“…Regarding platinum, most studies also employ peptide bolaamphiphilebased hydrogels. These materials are used to modulate the in situ synthesis of ultrafine platinum nanoparticles capable of catalysing the hydrogen evolution reaction [151] and hydrogenations [152]. For instance, Kori et al [151] reported the in situ synthesis of platinum nanoparticles in bolaamphiphile hydrogels that displayed excellent electrocatalytic activity in basic and neutral pH solution, as well as good stability for the electrochemical hydrogen evolution reaction, which has great potential for energy conversion applications.…”
Section: Composites For Electronic Catalytic and Environmental Applic...mentioning
confidence: 99%
See 1 more Smart Citation